2017
DOI: 10.1021/acssensors.7b00455
|View full text |Cite
|
Sign up to set email alerts
|

Nanopatterned Bulk Metallic Glass Biosensors

Abstract: Nanopatterning as a surface area enhancement method has the potential to increase signal and sensitivity of biosensors. Platinum-based bulk metallic glass (Pt-BMG) is a biocompatible material with electrical properties conducive for biosensor electrode applications, which can be processed in air at comparably low temperatures to produce nonrandom topography at the nanoscale. Work presented here employs nanopatterned Pt-BMG electrodes functionalized with glucose oxidase enzyme to explore the impact of nonrandom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…It is also important to note that recent reports on approaches to improve sensor sensitivity by way of increased surface area and biocompatibility on glass, graphene, and biomass-derived nanocomposites have demonstrated the unique utility of techniques, such as nanopatterning, activated carbon transition metal oxides, and graphene nanomesh technology [ 34 , 35 , 36 ]. These approaches improved biosensor sensitivity above standard protocols for electrodes, receptor-guided biomarkers, and small molecule detection.…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to note that recent reports on approaches to improve sensor sensitivity by way of increased surface area and biocompatibility on glass, graphene, and biomass-derived nanocomposites have demonstrated the unique utility of techniques, such as nanopatterning, activated carbon transition metal oxides, and graphene nanomesh technology [ 34 , 35 , 36 ]. These approaches improved biosensor sensitivity above standard protocols for electrodes, receptor-guided biomarkers, and small molecule detection.…”
Section: Resultsmentioning
confidence: 99%
“…Despite not being able to fully resolve the electrochemical processes for devices such as energy-storage or sensors, [8] these calculations could be useful for predicting boundary properties such as ion diffusion and double-layer morphology in the presence of an electric field to study the electrochemical reactions more in depth. Although not always reported, surface modifications were likely to occur.…”
Section: Can Computational Modeling and Advances In Mgns Help On Unramentioning
confidence: 99%
“…[4] In fact, many studies have shown that with reduction in size, nanomaterials display novel electrical, mechanical, chemical and optical properties, which are largely believed to be the result of surface and quantum confinement effects. [4,5] Remarkably, this trend has found traction in the metallic glass field where metallic glasses nanostructures (MGNs) demonstrate an important role in many applications such as light harvesting, [6] photovoltaic, [7] biomedical, [8] magneto-optical, [9] organic synthesis, [10] lithium-ion batteries [11] and electrocatalysis. [12] Recently, MGNs are receiving increased attention due to their distinguished performance, such as high activity and long term stability in electrocatalytic reactions.…”
mentioning
confidence: 99%
“…using platinum‐based BMGs to enhance the signal and sensitivity compared to planar electrodes, for the detection of glucose. [ 62 ]…”
Section: Materials Selection For Ec Biosensor Electrode Transducersmentioning
confidence: 99%